PHILOSOPHY AND SCIENCE IN EDUCATION: BETWEEN FRAGMENTATION AND COMPLEXITY - das Chagas , José Soares (Seven Editora, 2024)
This article aims to critically analyze the fragmentation of scientific and human knowledge, often confined to school disciplines and university departments, in the light of the history of the relationship between philosophy and science. To do so, we used the Cartesian paradigm and the emergence of the complexity paradigm as a reference. We investigate, in particular, the pedagogical models derived from the Cartesian paradigm, with emphasis on the pedagogy of competencies and skills that, with the reform of High School promoted by Mendonça Filho, became the official guideline of the school curriculum in Brazil. In this context, we question to what extent this curricular and pedagogical change can overcome the Cartesian model and whether the roles attributed to philosophy and science in these legal documents contribute to the articulation of knowledge from a perspective of complex thinking. DOI: https://doi.org/10.56238/sevened2024.037-092